Liquefaction Assessment Using the CPT and Accounting for Soil Ageing - Bambang Setiawan; Mark Jaksa (Graduate Program of Syiah Kuala University, 2018)
Due to its continuous data recording capability, excellent repeatability and accuracy, relatively low cost and simplicity of operation, the cone penetration test (CPT) offers enhanced liquefaction assessment over its predecessor the standard penetration test (SPT). However, soil ageing, which influences the cyclic resistance ratio (CRR), is difficult, if not impossible, to be detected by the CPT due to disturbance during the test. This situation may lead to excessively conservative estimation of CRR values which result in conservative assessment of liquefaction potential. This paper presents and discusses liquefaction assessment using the CPT and methods for accounting for soil ageing. A field study, conducted at Gillman, South Australia, is presented and the study site is assessed for liquefaction potential. This paper also explores the influence of soil ageing on the subsequent liquefaction assessment.